Optical and electrochemical detection of a verotoxigenic E. coli gene using DNAzyme-labeled stem-loops - Longinotti, Gloria (2017)
The activity of a peroxidase-mimicking DNAzyme was optimized to be used as a catalytic label in a stem-loop genosensor construction for quantifying the gene sequence Shiga-like toxin I of verotoxigenic E. coli. Experimental conditions such as pH, buffer composition, potassium ion concentration, and hemin-to-oligonucleotides ratio, were analyzed to maximize optical and electrochemical responses using microvolumes. Different stem-loop constructions were evaluated to obtain the optimum response against the target concentration. Linear ranges of 0.05-0.5 µM and limits of detection of 174 nM and 144 nM were estimated for the optical and electrochemical measurements, respectively. Selectivity was proved by assaying other verotoxigenic, enterotoxigenic and enteroinvasive sequences. The results show that, if a combination of small-volume electrochemical cells and low-cost untreated screen-printed electrodes with a relatively high geometric area is used, electrochemical measurements present similar sensitivity and limits of detection to the more usual optical ones, allowing the development of low-cost electrochemical biosensors based on the use of soluble DNAzymes as labels.